PENGEMBANGAN PENJENAMAAN DIRI AUTENTIK GENERASI Z DALAM MEDIA SOSIAL - Irena, Lydia; Alexandra Carolina (Jurnal Serina Abdimas, 2025)
In the digital era, social media has become a central platform for Generation Z to shape their identity and public self-image. However, the rapid flow of instant content and viral trends often leads to the creation of digital personas that are misaligned with their true values and potential. Many youth, especially high school students, struggle to build an authentic and sustainable personal brand, resulting in a reliance on external validation. To address this, a community engagement initiative was conducted at SMK Negeri 1 Cimahi, aiming to support students in developing purposeful and value-based personal branding. Grounded in personal branding theory—which emphasizes value consistency, competence, and personal differentiation—the program took the form of an interactive seminar. This seminar combined presentations, group discussions, and practical exercises focused on crafting personal branding strategies using social media. Participants were encouraged to recognize their uniqueness, define core personal messages, and choose the right digital platforms to express their professional identity. The participatory and needs-based approach aimed to foster greater self-awareness, confidence, and media literacy. Evaluation results showed a significant improvement in students’ understanding, with an increase in the average awareness score from 3.08 to 4.39. Participants demonstrated better comprehension of the meaning, importance, and key components of authentic personal branding. This suggests that the program effectively met its objectives and provided students with the tools to build meaningful, authentic digital identities. ABSTRAK Di era digital, media sosial menjadi ruang utama bagi Generasi Z dalam membentuk identitas dan menampilkan citra diri. Namun, derasnya arus konten instan dan budaya viral kerap membuat mereka kesulitan membangun penjenamaan diri yang autentik dan berkelanjutan. Akibatnya, terbentuk persona digital yang tidak selaras dengan nilai dan potensi pribadi, serta ketergantungan pada validasi eksternal. Kegiatan Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk mendampingi siswa sekolah menengah, khususnya di SMK Negeri 1 Cimahi, dalam mengembangkan personal branding yang otentik dan berbasis pemahaman diri. Kegiatan ini berlandaskan teori personal branding yang menekankan konsistensi nilai, kompetensi, dan diferensiasi diri dalam membangun citra yang kredibel di ruang digital. Metode yang digunakan adalah seminar interaktif dengan pemaparan materi, diskusi kelompok, dan praktik langsung dalam menyusun strategi personal branding melalui media sosial. Peserta diarahkan untuk mengenali keunikan diri, merumuskan pesan inti personal, dan memilih platform yang tepat untuk menampilkan identitas profesional mereka. Pendekatan yang partisipatif dan berbasis kebutuhan ini berhasil meningkatkan pemahaman peserta. Hasil evaluasi menunjukkan peningkatan skor rata-rata wawasan dari 3,08 menjadi 4,39, menandakan bahwa materi yang disampaikan relevan dan efektif. Peserta juga menunjukkan peningkatan pemahaman terhadap pengertian, urgensi, serta komponen penjenamaan diri yang autentik. Hal ini menunjukkan bahwa kegiatan ini mampu mentransfer pengetahuan dengan baik dan mendorong generasi muda untuk menjadi pribadi yang percaya diri, sadar nilai, dan cerdas dalam bermedia.